Reflection and importance of user interventions in changes and or transformations in temporary housing after the earthquake - Ayşe Merve Duru; Özlem Şenyiğit Sarıkaya (Frontiers of Architectural Research)
Temporary housing is one of the most important elements in disaster recovery and reconstruction activities in emergency situations. This study predicts that post-disaster housing and social life needs can be improved through user satisfaction analyses and underlines that user experiences can guide the achievement of better design solutions in temporary housing. In this context, the case study is based on an evaluation of the changes and/or transformations that took place as a result of the Lagoon Hobby Houses campus, built in the Kahramanmaraş Expo area, being opened to the use of disaster victims as temporary housing after the 2023 Kahramanmaraş earthquake. The findings suggest that improvements can be made in evidence- and experience-based design and post-disaster temporary housing design criteria by creating reserve areas for residences, designing common areas that encourage socialization and interaction, and providing access to green areas to overcome post-earthquake traumas more easily.